2018
DOI: 10.1039/c7nj04505k
|View full text |Cite
|
Sign up to set email alerts
|

Rhodamine based turn-on chemosensor for Fe3+ in aqueous medium and interactions of its Fe3+ complex with DNA

Abstract: A novel di-coordinating rhodamine-based chemosensor, HL with NO donor atoms, selectively and rapidly recognizes Fe3+ in the presence of all biologically relevant as well as toxic metal ions and numerous anions and also with other reactive oxygen and nitrogen species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…To demonstrate facile functionalization of the obtained hydrogel to provide a pH‐ and metal ion–sensing platform, a rhodamine derivative (RHB‐NH 2 ) was chosen. It is well established that the rhodamine moiety exhibits colorimetric response to acidic pH, as well as toward certain metal ions like Fe 3+ . This is easily observable by naked eye, as well as through UV–vis spectroscopy.…”
Section: Resultsmentioning
confidence: 98%
“…To demonstrate facile functionalization of the obtained hydrogel to provide a pH‐ and metal ion–sensing platform, a rhodamine derivative (RHB‐NH 2 ) was chosen. It is well established that the rhodamine moiety exhibits colorimetric response to acidic pH, as well as toward certain metal ions like Fe 3+ . This is easily observable by naked eye, as well as through UV–vis spectroscopy.…”
Section: Resultsmentioning
confidence: 98%
“…It was found that the bluish fluorescence of a solution of 1 could be sensed using minimum 3.16 μM of DNA using the equation DL = σ* Sb1/S, where σ = 3, Sb1 is the standard deviation of the intercept of the blank, and S is the slope of the calibration curve obtained from the linear dynamic plot , of fluorescence intensity vs [DNA]. Hence, the limit of detection was estimated to be 3.16 μM (Figure S6†).…”
Section: Resultsmentioning
confidence: 99%
“…As metal complexes are believed to be less poisonous compared to free ligands, there has been increased attention to progress the fresh biologically active complexes that can be utilized as fluorescent light-up probes. The complexes of transition-metal ions are well known to display significant roles in several physiological activities through the linkage of macromolecules. The transition-metal complexes of ruthenium, iridium, and osmium have been used as probes for DNA sensing. Electrochemical DNA probing has shown that the metal complexes that intercalate with DNA are more suitable than groove binding or external metal-binding complexes as the intercalator complexes bind a greater amount per DNA sequence and thus increase the detection limits in targeted DNA .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, to check the stability of spirolactam ring of P3 upon treating with F − ions 13 C‐NMR was carried out. The peat at 66.08 ppm in figure S9; supporting information which corresponds to quaternary carbon of spirolactam ring in probe P3 was observed even after treating with F − ions (65.56 ppm, figure S13; Supporting Information) . This clearly indicates that the spirolactam ring was not opened during the binding process.…”
Section: Sensing Of Anionsmentioning
confidence: 93%